Deep macrobenthic communities from Nazaré submarine canyon (NW Portugal) - Curdia, J (2012)
Macrofauna community structure within Nazare Submarine Canyon is analysed and used to assess the potential effects of natural enrichment in this area subjected to accumulation of coastal sediments. A transect including three stations (2894. 3514 and 4141 in) was carried out in the Nazare Submarine Canyon (NW Portugal) during a cruise of OMEX 11 programme (Ocean Margin Exchange), in the winter season of 1999. Although data was not collected in order to calculate sedimentation rates. sampling station at 2894 m is located in an area characterised by high levels of sedimentation, thus a high amount of organic matter is expected to be available for the local communities. Faunistic data are discussed in the context of the different features of the stations sampled. Multivariate analysis clearly separates the shallowest station from the other ones. which otherwise appear to be very similar. It also revealed a perceptible gradient along sediment depth at all stations. from shallow to deeper layers. Exceptionally depressed species richness and low evenness Values were observed at the 2894 m station. The high number of individuals of a single species, Cossura sp. A. and the atypical diversity, dominance and evenness values obtained for this station Support the hypothesis of community disturbance due to organic enrichment.